Cardiorespiratory fitness and incident metabolic syndrome in middle-aged Korean men. (September 2014) - Jae, Sae Young; Heffernan, Kevin S.; Kim, Do-Kyung; Park, Won Hah; Choi, Yoon-Ho; Kim, Seol Hyang
Abstract This study investigated the relationship of cardiorespiratory fitness (CRF) with incident metabolic syndrome in 810 middle aged Korean men. All subjects were free of metabolic syndrome at baseline examination. The metabolic syndrome was defined by NCEP criteria and CRF was directly measured by peak oxygen uptake during a treadmill test. During an average of 3.3 years of follow-up, 155 (19.1%) men developed the metabolic syndrome. The incidence of metabolic syndrome was inversely associated with CRF quartiles (p < 0.05). The relative risk (RR) of incident metabolic syndrome in the lowest CRF quartile vs the highest CRF quartile was 1.67 (95% CI = 1.07–2.60) after adjustment for covariates. Each metabolic equivalent (MET) increment in peak oxygen consumption was associated with a 17% (RR = 0.83, 95% CI = 0.73–0.94) lower incidence of metabolic syndrome. These results demonstrate that cardiorespiratory fitness was associated with the incidence of metabolic syndrome independent of covariates in middle aged Korean men.